Metasurface-based ultra-lightweight high-gain off-axis flat parabolic reflectarray for microwave beam collimation/focusing - Silva, Sinhara R. (Sci Rep, 2019)
Ultra-lightweight deployable antennas with high-gain are pivotal communication components for small satellites, which are intrinsically constrained in size, weight, and power. In this work, we design and demonstrate metasurface-based ultra-lightweight flat off-axis reflectarrays for microwave beam collimation and focusing, similar to a parabolic dish-antenna. Our ultra-thin reflectarrays employ resonators of variable sizes to cover the full 2π phase range, and are arranged on the metasurface to realize a two-dimensional parabolic focusing phase distribution. We demonstrate a 30° off-axis focusing reflector that exhibits a measured gain of 27.5 dB at the central operating frequency of 11.8 GHz and a 3 dB directionality <[Formula: see text] 1.6°. Furthermore, we carry out full-wave simulations of the reflectarray, showing high gain of the beam focusing/collimation functionality, in good agreement with measurements. The demonstrated reflectarrays will enable low-cost, lightweight, and high-gain deployable transceivers for small-satellite platforms.